A study on the boycott motivations of Malaysian non-Muslims - Abdul-Talib, Asmat-Nizam; Abd-Latif, Samshul-Amry; Abd-Razak, Ili-Salsabila (Emerald Group Publishing Ltd., 2016)
Purpose This paper aims to examine non-Muslim consumers’ willingness and motivation to boycott American-based companies operating in Malaysia, where Islam is prominent. The underlying base used in this study is an on-going boycott spurred by the Palestinian/Israel conflict in the Middle East.